Synthesis of various types of green biosorbents materials for removals of sulphates from contaminated water for better aquatic environments - Subhashish Dey; G.T.N. Veerendra; A.V. Phani Manoj; Siva Shanmukha Anjaneya Babu Padavala (Waste Management Bulletin, 2024)
Human and industrial activities pollute water resources with sulphur metal, endangering human health and ecosystems. Chemical precipitation and membrane filtration are expensive when treating large amounts of water, inefficient at low metal concentrations, and produce large amounts of toxic sludge and other products that must be disposed of waste water bio-sorption is eco-friendly and alternative. These methods are cheaper, more accessible, and reusable than conventional ones. This study investigates the bio-sorption of sulphur from contaminated water using neem leaf, custard apple leaf, mango tree leaf, orange peels, and banana peels biological waste materials. This work achieves 100 % removal efficiency. Biosorbents remove sulphates from contaminated water: custard leaves 100 % at 4gm, orange peels 40 % at 5gm, tea waste 50 % at 4gm, neem leaves 70 % at 5gm, and mango leaves 75 % at 5gm. The performances of biosorbents for removals of sulphates from water as follows: Custard leaves waste > Mango leaves > Neem leaves > Tea trash > Orange peels the sulphate reduction by biosorbents. The best biosorption occurred at basic pH 6.5, 3.7gm dosage, 90 min contact duration, 30 °C temperature, and 120 rpm agitation speed. The effects of contact time, agitation speed, adsorbent dosage, pH, and temperature are also examined. Before usage, biosorbents materials can be physically and chemically measured the changes. Regenerating and reusing bio-sorbent after sulphates removals makes the method cost-effective for removals of pollutants from water.